INTEGRATIVE QSAR ANALYSIS OF OXADIAZOLE DERIVATIVES: RESOLVING MOLECULAR DETERMINANTS FOR ANTI-TUBERCULAR ACTIVITY AND RATIONAL DRUG DESIGN - SUVARNA, NEHA H.; RAJ, VIKSHITH; HAREES, SHIHABUDHEEN; MATHEW, JESSY ELIZABETH; KUMAR, LALIT; VERMA, RUCHI (International Journal of Applied Pharmaceutics, 2024)
Objective: In this study, we conducted a comprehensive Quantitative Structure-Activity Relationship (QSAR) analysis of an oxadiazole derivative exhibiting potent anti-tubercular activity by inhibiting synthesis. Methods: Our investigation employed both 3D atom-based and field-based Comparative Molecular Field Analysis/Comparative Molecular Similarity Indices Analysis (CoMFA/CoMSIA) techniques, along with auto QSAR analysis using a 2D canvas. The CoMFA and CoMSIA methodologies allowed for the exploration of molecular interactions and structural features contributing to the molecule's inhibitory potency. Utilizing these 3D approaches, we delineated the steric, electrostatic, hydrophobic, and hydrogen bond acceptor/donor fields influencing the molecular activity. Furthermore, the auto QSAR analysis provided valuable insights into the 2D structural descriptors governing the anti-TB efficacy of the oxadiazole compound. Results: Our findings not only elucidate the molecular determinants essential for inhibitory activity but also provide a robust predictive model for assessing the anti-TB activity of structurally related compounds. Both 3D QSAR and 2D QSAR models were designed and generated. These models were found to be useful in predicting the anti-TB activity of oxadiazole derivatives. The best model for accurately predicting activity was found to have a Q² value of 0.9558 and an R² value of 0.979. Conclusion: This integrative QSAR study contributes to the rational design and optimization of novel oxadiazole-based therapeutics against tuberculosis, addressing the urgent need for effective treatment strategies against this global health threat.